Funkcje dwukropka w polskich opracowaniach normatywnych dotyczących interpunkcji (1770–1935) - Kinga Tutak (Ksiegarnia Akademicka Publishing, 2017)
Functions of the Colon in Polish Prescriptive Works on Punctuation (1770–1935) The paper investigates the function assigned to the colon in Polish prescriptive works on the rules of punctuation published between 1770 and 1935. Following the authors of grammar textbooks, spelling rules and punctuation treatises, three primary functions of the colon have been distinguished: the colon as an indicator of a citation, enumeration, and as an announcement of the forthcoming explanation of the previous sentence. The colon could constitute the sole signal of text delimitation, but it was also sometimes paired with the lexical environment, especially with metatextual elements. Treatises on punctuations also emphasized the role played by the colon in the rhetoric period.